Catching up, spillovers and innovation networks in a schumpeterian perspective - Pyka, Andreas; Fonseca, Maria da Graça Derengowsk (Springer eBook., 2011)
This book discusses the influence of technological and institutional change on development and growth, the impact on innovation of labor markets, the spatial distribution of innovation dynamics, and the meaning of knowledge generation and knowledge diffusion processes for development policies. The individual articles demonstrate the powerful possibilities that emerge from the toolkit of evolutionary and Schumpeterian economics. The book shows that evolutionary economics can be applied to the multi-facetted phenomena of economic development, and that a strong orientation on knowledge and innovation is key to development, especially in less developed and emerging economies.